Lighting of cultural heritage as a tool to exhibit historical architectural values in the context of creative industries (the case of Ukmergė) - Valevičius, Martynas; Levickaitė, Rasa (Creativity Studies, 2011)
The aim of the article is twofold: 1) to overview some ideas on creative industries and its major group – cultural heritage which is the soul of cultural and creative industries; in the context of creative economy an idea is proposed that a result of creative industries might enrich creative cultural project with additional value and generate valuable output; 2) to present a case study of Ukmergė city. The object of this article is to propose some ideas how an additional value is created which might enrich the urban project both in intangible and physical outcomes, e. g. the impact of urban lighting of public spaces. Many authors coming from a wide variety of perspectives have written about the very complex notion of public spaces, but authors of this article are focused on a role of artificial lighting which plays as a catalyst for increasing the awareness of the beauty and diversity of public spaces seen from the city: this stimulus encourages to rediscover and newly perceive the public spaces and the urban environment at night-time. Case study is based on Architectural-Urban Solution Creation and Development of Territory of Ukmergė Mound Project initiated by Ukmergė Municipality in 2010.Kultūrinio paveldo apšvietimas kaip priemonė atskleisti istorines architektūros vertybes kūrybinių industrijų kontekste (Ukmergės atvejis)Santrauka. Straipsnio tikslas dvilypis: pirma, apžvelgiamos kūrybinės industrijos; dėmesys kreipiamas į kultūros paveldo kūrybinių industrijų grupę, kuri yra miestų ir vietovių patrauklumo pagrindas. Antra, pristatomas Ukmergės miesto atvejis. Teigiama, kad kūrybinės industrijos turi potencialą kurti pridėtinę vertę aptariamuoju atveju panaudojant kultūrinio paveldo apšvietimą kaip priemonę atskleisti miesto istorines architektūros vertybes. Šio straipsnio autoriai pagrindinį dėmesį kreipia į viešųjų erdvių apšvietimą, kurio, kaip savotiško katalizatoriaus vaidmuo viešųjų erdvių kūrime, dėka išryškėja viešųjų erdvių grožis, jų savitumas, įvairovė ir kitos kultūros vertybės, vieta tampa patrauklia miesto gyventojams ir svečiams. Ukmergės atvejo analizė yra grindžiama Ukmergės piliakalnio teritorijos architektūrinio-urbanistinio sprendimo sukūrimo ir įgyvendinimo paslaugų projektu, kurį 2010 metais iniciavo Ukmergės miesto savivaldybė.Reikšminiai žodžiai: kūrybinės industrijos, istorinis paveldas, apšvietimas, miesto dizainas, miesto studijos.First published online: 11 Jan 2012